Polychlorinated Biphenyls and Attention Deficits - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The effects of in utero exposure to polychlorinated biphenyls (PCBs) on cognitive function in 212 children at 11 years of age were tested at Wayne State University, Detroit, MI.